ANTHROPOLOGIC TURN IN PHILOSOPHY: TOWARDS THEORY OF PUBLIC ADMINISTRATION - Kozyrieva N.V. (Pressing Problems of Public Administration, 2016)
This article analyzes historical development of the European humanitarian thought and American economic theory of institutionalism that led to an anthropologic turn, particularly in public administration.